Dexamethasone inhibits brain apoptosis in mice with eosinophilic meningitis caused by Angiostrongylus cantonensis infection - Tsai, Hung-Chin (Parasit Vectors, 2015)
BACKGROUND: Angiostrongylus cantonensis, the rat lungworm, is the major cause of eosinophilic meningitis worldwide. Rats serve as the definitive host of the nematode, but humans can be infected incidentally, leading to eosinophilic meningitis. A previous BALB/c animal study has demonstrated increased apoptotic proteins and decreased anti-apoptotic proteins in mice infected with A. cantonensis. Steroids may be an effective treatment option for eosinophilic meningitis caused by A. cantonensis, but the involved mechanism is unclear. This study hypothesized that the beneficial effects of steroids on eosinophilic meningitis are mediated by decreased apoptosis. METHODS: In a BALB/c animal model, mice were orally infected with 50 A. cantonensis L3 via an oro-gastric tube and were sacrificed every week for 3 consecutive weeks after infection or until the end of the study. Dexamethasone was injected intra-peritoneally from the 7(th) day post-infection until the end of the 21-day study. Evans blue method was used to measure changes in the blood brain barrier, while western blotting, immuno-histochemistry, and TUNEL assay were used to analyze brain homogenates expression of apoptotic and anti-apoptotic proteins. RESULTS: There were increased amounts of Evans blue, apoptotic proteins (caspase-3, -8, and -9 and cytochrome C), and decreased anti-apoptotic proteins (bcl-2) after 2-3 weeks of infection. Dexamethasone administration significantly decreased Evans blue extravasations and apoptotic protein expressions. CONCLUSIONS: Apoptosis of mice brain homogenates can be repressed by dexamethasone treatment.